Multi-Omics Analysis of Diabetic Nephropathy Reveals Potential New Mechanisms and Drug Targets - Sha, Qian; Lyu, Jinxiu; Zhao, Meng; Li, Haijuan; Guo, Mengzhe; Sun, Qiang (Frontiers in Genetics, 2020)
Diabetic nephropathy (DN) is one of the most common diabetic complications, which is the major course of end-stage renal disease (ESRD). However, the systematical molecular characterizations during DN pathogenesis and progression has not been not well understood. To identify the fundamental mediators of the pathogenesis and progression of DN. we performed a combination RNASeq, proteomics, and metabolomics analyses of both patients’ derived kidney biopsy samples and kidneys from in vivo DN model. As a result, molecular changes of DN contain extracellular matrix accumulation, abnormal activated inflamed microenvironment, and metabolism disorders, bringing about glomerular sclerosis and tubular interstitial fibrosis. Specificity. Further integration analyses have identified that the linoleic acid metabolism and fatty-acids b-oxidation are significantly inhibited during DN pathogenesis and progression, the transporter protein ABCD3, the fatty acyl-CoA activated enzymes ACOX1, ACOX2, and ACOX3, and some corresponding metabolites such as 13’-HODE, stearidonic acid, docosahexaenoic acid, (±)10(11)- EpDPA were also significantly reduced. Our study thus provides potential molecular mechanisms for DN progression and suggests that targeting the key enzymes or supplying some lipids may be a promising avenue in the treatment of DN, especially advanced-stage DN.